1973
DOI: 10.1090/s0002-9947-1973-0338058-9
|View full text |Cite
|
Sign up to set email alerts
|

Prime ideals and sheaf representation of a pseudo symmetric ring

Abstract: ABSTRACT. Almost symmetric rings and pseudo symmetric rings are introduced.The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(40 citation statements)
references
References 10 publications
0
38
0
Order By: Relevance
“…A prime ideal P of a ring R is called completely prime if R/P is a domain. Shin [19,Proposition 1.11] proved that a ring R is 2-primal if and only if every minimal prime ideal of R is completely prime. Lambek [13] called a ring R symmetric when rst = 0 implies rts = 0 for all r, s, t ∈ R, proving that a ring R is symmetric if and only if r 1 r 2 · · · r n = 0, with n any positive integer, implies r σ (1) r σ (2) · · · r σ (n) = 0 for any permutation σ of the set {1, 2, .…”
Section: Basic Structure Of Ni Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prime ideal P of a ring R is called completely prime if R/P is a domain. Shin [19,Proposition 1.11] proved that a ring R is 2-primal if and only if every minimal prime ideal of R is completely prime. Lambek [13] called a ring R symmetric when rst = 0 implies rts = 0 for all r, s, t ∈ R, proving that a ring R is symmetric if and only if r 1 r 2 · · · r n = 0, with n any positive integer, implies r σ (1) r σ (2) · · · r σ (n) = 0 for any permutation σ of the set {1, 2, .…”
Section: Basic Structure Of Ni Ringsmentioning
confidence: 99%
“…For a 2-primal ring R Sun [21,Theorem 2.3] showed that R is pm if and only if Spec(R) is a normal space if and only if the maximal ideal spectrum of R is a retract of Spec(R), where Spec(R) is the prime spectrum of R. We apply the topological methods of Sun [21] and Shin [19] to analyze these conditions for NI rings, relating to the space of strongly prime ideals of R in place of Spec(R).…”
Section: Topological Conditions For Ni Ringsmentioning
confidence: 99%
“…In recent years, a growing number of articles have studied the class of rings that is associated with the set N (R) of all nilpotent elements of a ring R . In 1973, Shin [21] proved that the prime radical P (R) coincides with the set of all nilpotent elements of R if and only if every minimal prime ideal is completely prime. In 1993, the term 2-primal, which satisfies P (R) = N (R) , was created by Birkenmeier et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this note, we find there are many researchers worked and attempted to find some results concerning semicommutative rings. G. Shin [57] showed for a ring R the following statements are equivalent: (i) R is semicommutative. (ii) For any a, b ∈ R, ab = 0 implies aRb = 0.…”
Section: Permuting N-semigeneralized Semiderivation Of (στ)-Semicommmentioning
confidence: 99%